2021
DOI: 10.1002/tpg2.20095
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of genome sizes and gradual gain of cell‐specific distribution of C4 enzymes during C4 evolution in genus Flaveria

Abstract: C 4 plants are believed to have evolved from C 3 plants through various C 3 -C 4 intermediate stages in which a photorespiration-dependent CO 2 concentration system known as C 2 photosynthesis operates. Genes involved in the C 4 cycle were thought to be recruited from orthologs present in C 3 species and developed cell-specific expression during C 4 evolution. To understand the process of establishing C 4 photosynthesis, we performed whole-genome sequencing and investigated expression and mesophyll-or bundle-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…It clearly outcompetes its parental lineages in terms of C 4 physiology. Taniguchi et al (2021), studying genome size evolution in Flaveria , showed dynamic alteration of genome size in the genus with F. brownii having the largest genome size among the 11 species investigated. Rewiring the parental genomes might have led to the C 4 -like phenotype found in F. brownii and might have facilitated adaptive divergence resulting in colonization of the coastal flats and islands of the lower Texas Gulf Coast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It clearly outcompetes its parental lineages in terms of C 4 physiology. Taniguchi et al (2021), studying genome size evolution in Flaveria , showed dynamic alteration of genome size in the genus with F. brownii having the largest genome size among the 11 species investigated. Rewiring the parental genomes might have led to the C 4 -like phenotype found in F. brownii and might have facilitated adaptive divergence resulting in colonization of the coastal flats and islands of the lower Texas Gulf Coast.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive molecular phylogenetic studies of Flaveria published so far were either based on few molecular markers only (McKown et al, 2005), or on concatenated data matrices and inference methods unable to reveal tree discordance, possible reticulation, or incomplete lineage sorting (Lyu et al, 2015). Irrespective of this, numerous current studies of evolutionary change during the establishment of the C 4 pathway rely on the Flaveria model (e.g., Lyu et al, 2021; Taniguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1A). The expression of all three PGR5 genes identified in the Flaveria genome (PGR5A, PGR5B, and PGR5C; Taniguchi et al, 2021) was suppressed in the PGR5-RNAi lines. The protein levels of PGR5, PGRL1, and NdhH were undetectable or less than 6% of the WT levels in the PGR5-RNAi, PGRL1-RNAi, and NdhO-RNAi lines, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to a lack of genome reference, current knowledge of the regulation of photosynthesis genes in this genus is still very limited. The first version of Flaveria genome references, including four species, were published recently (Taniguchi et al, 2021), and provide valuable resources for protein coding gene predictions for this genus. However, as these genomes were generated using short-read whole genome-sequencing, the assembled genomes are fragmented, which compromises their potential application (Taniguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The first version of Flaveria genome references, including four species, were published recently (Taniguchi et al, 2021), and provide valuable resources for protein coding gene predictions for this genus. However, as these genomes were generated using short-read whole genome-sequencing, the assembled genomes are fragmented, which compromises their potential application (Taniguchi et al, 2021). Taking advantage of long-read genome sequencing technology, here we reported chromosome-scale genome references of five Flaveria species, with which we conducted a systematic study of CREs and TFs during the evolution of C 4 photosynthesis.…”
Section: Introductionmentioning
confidence: 99%